2018
DOI: 10.1080/20010001.2018.1533754
|View full text |Cite
|
Sign up to set email alerts
|

Continuous overexpression of thioredoxin 1 enhances cancer development and does not extend maximum lifespan in male C57BL/6 mice

Abstract: We examined the effects of continuous overexpression of thioredoxin (Trx) 1 on aging in Trx1 transgenic mice [Tg(TXN)+/0]. This study was conducted to test whether increased thioredoxin expression over the lifespan in mice would alter aging and age-related pathology because our previous study demonstrated that Tg(act-TXN)+/0 mice had no significant maximum life extension, possibly due to the use of actin as a promoter, which may have resulted in loss of Trx1 overexpression during aging. To test this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 45 publications
(71 reference statements)
2
30
0
Order By: Relevance
“…The cross-sectional pathological analyses of 23 Tg(TXN) +/0 and 19 WT mice (22-24 months old) showed that the major disease in these mice was neoplastic disease. The tumors observed were lymphoma, hemangioma/ hemangiosarcoma in the liver and spleen, pulmonary ad-enocarcinoma, hepatocellular carcinoma, and adenoma in the thyroid gland, and the most prevalent tumor was lymphoma, which is consistent with the pathology data from C57BL/6 mice and mice overexpressing Trx1 [11,13]. First, we compared the number of different types of tumors (tumor burden) for each mouse in both Tg(TXN2) +/0 and WT groups because aging mice may have several different types of tumors.…”
Section: Cross-sectional Pathologysupporting
confidence: 87%
See 2 more Smart Citations
“…The cross-sectional pathological analyses of 23 Tg(TXN) +/0 and 19 WT mice (22-24 months old) showed that the major disease in these mice was neoplastic disease. The tumors observed were lymphoma, hemangioma/ hemangiosarcoma in the liver and spleen, pulmonary ad-enocarcinoma, hepatocellular carcinoma, and adenoma in the thyroid gland, and the most prevalent tumor was lymphoma, which is consistent with the pathology data from C57BL/6 mice and mice overexpressing Trx1 [11,13]. First, we compared the number of different types of tumors (tumor burden) for each mouse in both Tg(TXN2) +/0 and WT groups because aging mice may have several different types of tumors.…”
Section: Cross-sectional Pathologysupporting
confidence: 87%
“…The severity of lymphoma was slightly higher in Tg(TXN2) +/0 mice compared to WT mice, although the difference was not statistically significant. These pathological observations indicate that overexpression of Trx2 in mitochondria may play a similar role in the development and growth of lymphoma as the overexpression of Trx1 [11,13], i.e., accelerate the growth and development of lymphoma as they age. Subsequently, we measured several signaling pathways (i.e., mTOR, NFκB, and c-Jun/Fos) because substantial evidence shows that these pathways play important roles in cancer development and lifespan and can also be attenuated by Trx.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The study showed that the survival curve of Tg(TXN) +/0 mice was not significantly different from WT mice. Although the early part of lifespan (75% survival) showed a 6.3% extension compared to WT mice, no significant life-extending effect was observed over the lifespan [16]. Therefore, our survival data obtained from Tg(TXN) +/0 mice indicate that continuous Trx1 overexpression in mice had some benefits only in the early part of life.…”
Section: Transgenic Mice/rats Overexpressing Thioredoxin 1 (Cytosol)mentioning
confidence: 64%
“…Next, we generated a new line of Trx1 transgenic mice (Tg(TXN) +/0 ) in order to determine whether continuous overexpression of Trx1 throughout life could extend maximum lifespan. These mice were generated using a fragment of the human genome containing the TXN gene [16]. Tg(TXN) +/0 mice showed significantly higher (approximately 20% to 40%) levels of Trx1 in the tissues than WT mice.…”
Section: Transgenic Mice/rats Overexpressing Thioredoxin 1 (Cytosol)mentioning
confidence: 99%